Social and Economic Views of V. Čepinskis (in Commemoration of the Professor’s 130 Anniversary of Birth) - Martišius, Stanislovas (Ekonomika, 2001)
The article describes social and economic views or Prof. V. Čepinskis, focuses on his social aspirations and discusses his views on the methodology of scientific cognition. It is stated that V. Čepinskis’ views represent the democratic socialism trend. V. Čepinskis positively valued T.R. Malthus’ theory on the development of population; in his opinion failure to provide much evidence on the human nature is the biggest blunder of science. In the theory of scientific cognition V. Čepinskis applied methodology of natural sciences for the study of social phenomena. Generally, Prof. V. Čepinskis viewpoint towards society was of synthetic nature, he maintained that social phenomena should be studied from various aspects. He searched for the common contact points in science and religion, opposed the authoritarian rule and always protected personal freedom and fought for the ideals of social justice.